Promoting physical activity in people with intellectual and multiple disabilities through a basic technology-aided program. (June 2018) - Lancioni, Giulio E; Singh, Nirbhay N; O'Reilly, Mark F; Sigafoos, Jeff; Alberti, Gloria; Perilli, Viviana; Zimbaro, Carmen; Boccasini, Adele; Mazzola, Carlo; Russo, Roberto
This study assessed a technology-aided program (monitoring responding, and ensuring preferred stimulation and encouragements) for promoting physical activity with 11 participants with severe/profound intellectual and multiple disabilities. Each participant was provided with an exercise device (e.g. a static bicycle and a stepper) and exposed to the program according to an ABAB design, in which A and B represented baseline and intervention phases, respectively. Data recording concerned (a) the participants' responses with the exercise device (e.g. pedaling) during baseline and intervention phases and (b) their heart rates during the last intervention phase. The results showed that all participants had significant increases in responding with the exercise devices during the intervention phases. Heart-rate values during the intervention sessions indicated that the participants' responding during those sessions mostly amounted to moderate-intensity physical activity, with potential benefits for their overall physical condition. Implications of the findings and questions for future research in the area were discussed.